Tryptophan: The Molecular Key to Unlocking Superior Sleep, Mood Enhancement and Athletic Recovery - Mateusz Drabczyk; Karolina Karoń; Anna Zygmunt; Łukasz Karoń; Emilia Pedrycz; Wojciech Grabowski; Daria Pedrycz; Grzegorz Drapała; Sławomir Karoń (Journal of Education, Health and Sport)
Tryptophan, an essential amino acid, plays a pivotal role in regulating sleep, mental health, athletic recovery and age-specific health conditions. Sleep, a fundamental biological process critical for physical and mental well-being, is intricately linked to the availability and metabolism of tryptophan. This amino acid serves as a precursor for serotonin, a neurotransmitter involved in mood regulation and melatonin, a hormone governing the sleep-wake cycle. Tryptophan’s conversion to serotonin and subsequent synthesis of melatonin underscore its influence on circadian rhythm stabilization and sleep quality enhancement.  Emerging evidence supports the therapeutic potential of tryptophan supplementation in managing insomnia, optimizing recovery in athletes, and alleviating symptoms of irritable bowel syndrome (IBS). Its role in athletic recovery is particularly significant, as improved sleep quality accelerates tissue repair and enhances overall performance. Moreover, tryptophan demonstrates age-specific benefits, addressing sleep disturbances prevalent in older adults and contributing to improved mental health outcomes across various life stages. The modulation of serotoninergic pathways by tryptophan also underscores its broader implications for mood regulation and neuropsychiatric disorders.